"We No Longer Respect the Law": The Tilco Strike, Labour Injunctions, and the State - Sangster, Joan (Labour/Le Travailleur, 2004)
Abstract In 1967 a strike of marginalized women workers in small-town Ontario became a cause célèbre for the Ontario and national labour movements due to the employers’ use of an ex parte injunction to break the strike, and the trade union movement’s subsequent legal challenge to that injunction. This article explores the initial Tilco strike in Peterborough, the ensuing attempts by the labour movement to support the striking local of the Textile Workers Union of America (TWUA), the criminal trials of those arrested for disobeying the injunction, and the Ontario Royal Commission on Labour Disputes which followed, chaired by Justice Ivan Rand. These events serve as a useful window through which to view labour-capital relations in this period, particularly the way in which the “Fordist” accord was profoundly gendered. Tilco also reveals a labour movement strengthened by post-World War II industrial legality, but challenged from its own margins by dissatisfaction of the rank and file with that same industrial legality. Finally, Tilco and the ensuing battle over injunctions highlights interpretive debates in Canadian working-class history concerning the state, the legal regulation of labour, and the potential malleability of state institutions in the face of pressures for reform.